In how many ways is it possible to tell the History of Ancient Africa? - Nepomoceno Pina, Edjalma (Romanitas - Revista de Estudos Grecolatinos, 2022)
Book review of: FURLANI, João Carlos (org.). A África no Mundo Antigo: possibilidades de ensino e pesquisa. Serra: Milfontes, 2019. 238 p.